AB0664 REYNOLDS SYNDROME: ABOUT 7 CASES. (June 2019) - hela, KCHIR; Gharbi, Ons; Cherif, Dhouha; Issaoui, Dhilel; Limaiem, Faten; Kaffel, Dhia; Maamouri, Nadia
Abstract : Background: Reynolds syndrome is a rare condition defined by the association of primary biliary cholangitis (PBC) with CREST syndrome. The frequency of scleroderma during PBC varies between 3 and 17%. The diagnosis is most often done during systematic search for autoimmune diseases associated with CBP. Objectives: To determine the epidemiological, clinical, paraclinical and evolutionary features of Reynolds syndrome Methods: We report 7 cases of Reynolds syndrome collected in the our department between 1996 and 2014 Results: There were 7 middle-aged women with an average age of 49.2 years (32-61 years old). The diagnosis of CREST syndrome with anti centromeric positive antibodies was retained in 6 cases. Extensive trunk sclerosis associated with diffuse sclerodacty and anti centromeric antibodies was noted in 1 case. An isolated acrosyndrome was noted in 1 case. The hepatic assessment found non icteric cholestasis in 6 patients. Anti-mitochondrial antibodies type M2 were positive in 6 cases. Liver biopsy showed histologic lesions consistent with primary biliary cholangitis PBC in 5 cases. Sjörgen's syndrome was confirmed histologically in 1 case. Autoimmune diseases (rheumatoid arthritis and lymphocytic thyroiditis) were associated with Reynolds Syndrome in 2 cases. The treatment consisted of ursodeoxycholic acid alone (N = 4), or combined with D-penicillamine (N = 1), azathioprine-associated prednisone (N = 1) or a calcium channel blocker alone (N = 1). The evolution was favorable in 2 cases. In the other 3 patients, worsening of cholestasis and complications such as oedemato-ascitic decompensation and gastrointestinal haemorrhage were noted during the course of the study. One patient died of cataclysmic gastrointestinal bleeding by rupture of oesophageal varices. Conclusion: Reynolds syndrome is a rare entity that should be discussed in the presence of liver function disturbances in patients with CREST syndrome. Conversely, the CREST syndrome should be referred to and sought systematically in case of PBC. Disclosure of interests: None declared